Reliable and Damage-Free Estimation of Resistivity of ZnO Thin Films for Photovoltaic Applications Using Photoluminescence Technique. (19th February 2013) - Poornima, N.; Vimalkumar, T. V.; Rajeshmon, V. G.; Kartha, C. Sudha; Vijayakumar, K. P.
Abstract : This work projects photoluminescence (PL) as an alternative technique to estimate the order of resistivity of zinc oxide (ZnO) thin films. ZnO thin films, deposited using chemical spray pyrolysis (CSP) by varying the deposition parameters like solvent, spray rate, pH of precursor, and so forth, have been used for this study. Variation in the deposition conditions has tremendous impact on the luminescence properties as well as resistivity. Two emissions could be recorded for all samples—the near band edge emission (NBE) at 380 nm and the deep level emission (DLE) at 500 nm which are competing in nature. It is observed that the ratio of intensities of DLE to NBE (I DLE /I NBE ) can be reduced by controlling oxygen incorporation in the sample. I -V measurements indicate that restricting oxygen incorporation reduces resistivity considerably. Variation of I DLE /I NBE and resistivity for samples prepared under different deposition conditions is similar in nature. I DLE /I NBE was always less than resistivity by an order for all samples. Thus from PL measurements alone, the order of resistivity of the samples can be estimated.